Characterization of Seabuckthorn (Hippophae spp.) genetic resources in India using morphological descriptors - Mathew D.=700 1 Parimelazhagan, T.; Gomez, S.
(En, Fr, Es)
ilus., 33 ref.
Keywords: RECURSOS GENETICOS; VARIACION GENETICA; HIPPOPHAE; FRUTO; VALOR NUTRITIVO; ANTIOXIDANTES; INDIA; ESPINO AMARILLO